Estudo morfométrico e do desenvolvimento de potros campeões da raça Mangalarga Marchador - Kate Moura da Costa Barcelos (2016)
The knowledge of the conformation at different stages of horse`s life can assist in early selection of breeding animals and an evaluation of morphological conditions that predispose injury during a training phase. Already the knowledge of age at which the growth of major long bones ends is of great value in planning the training intensity and/or release to start the formal training and horseback riding. In the Mangalarga Marchador (MM) breeding it is common to have many young horses participate in the competitions and a lack of scientific knowledge in the preparation of this horses for participation in exhibitions has justified this work which consists of three chapters. In Chapter I, the conformational value of 423 foals was evaluated. These foals were MM breed champions of 15 to 60 months of age, with 122 the marcha picada type of gait (MP) (67 females and 55 males) and 301 of the gait type marcha batida (MB) (154 females and 147 males). These foals were divided into 8 groups of different age ranges, evaluating by gender and the type of gait (marcha batida or marcha picada). 4 of these groups showed leading by hand and other 4 were ridden. The horses were measured during the national exhibitions in 2014 and 2015 held at the Parque Bolivar de Andrade in Belo Horizonte, Minas Gerais State. Thus, all the horses, males and females that won awards: champion, reserve champion, 1st, 2nd, 3rd, 4th and 5th awards, were measured with 21 linear measuments, 9 angular measurements and 3 diameter measuraments totaling 33 measures plus 18 indexes. The values were compared with the ideal MM model of Santiago (2013) and Santiago et al.. (2014) and with the proportions described by Lesbre (1930) for the saddle horses, in order to explain how variations in the morphometric measurements of the growing horses until an adult age. In Chapter II was estimated the period of closure of epiphyseal plate of the radial and tibia bones. For this reason, 56 marcha picada horses were analyzed in the distal region of the radius and tibia, between 18 and 58 months, classified into seven award categories: champion, reserve champion, 1st, 2nd, 3rd, 4th and 5th awards at the National Exposition in 2014. In Chapter III, the aim was associate the angulation of the hock with an occurrence of orthopedic diseases in animals x-rayed in Chapter II. The experimental design was completely randomized. For the chapter I, the analysis was done by type of gait considering a 2 x 8 factorial scheme (both sexes and 8 age classes). Body measurements were subjected to descriptive analyzes and variance, and the means were compared by the Tukey test (p <0.05). The closure of epiphyseal plates was classified into: A- fully open, B- partially closed C- fully closed and analyzed descriptively. Associations of morphometric measurements with diseases of the hock were compared by the Fisher test (p <0.05). The results of this study were used for the early morphological selection of breeding horses; adjustments in management and feeding of foals; planning of training in accordance with conformation and age of each horse, preventing injuries and improving as conditions for the well-being of the Mangalarga Marchador breed.